2011
DOI: 10.1097/id.0b013e31820fb99e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Microorganism Species Succession on Three Implant Surfaces With Different Roughness: An In Vivo Study

Abstract: The surface roughness does not affect the bacterial species succession in the biofilm. The succession of species was similar during all periods of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Additionally, two studies did not find significant superiority between titanium and zirconia [42,51]. When compared to a different dental material called hydroxyapatite, only zirconia, not titanium, displayed superiority in lowering bacterial biofilm on the implant surfaces [13,43]. In another study, copper-based surfaces exhibited greatly decreased bacterial biofilm compared to titanium [16].…”
Section: Comparison Of Titanium With Other Implant Surface Materialsmentioning
confidence: 95%
“…Additionally, two studies did not find significant superiority between titanium and zirconia [42,51]. When compared to a different dental material called hydroxyapatite, only zirconia, not titanium, displayed superiority in lowering bacterial biofilm on the implant surfaces [13,43]. In another study, copper-based surfaces exhibited greatly decreased bacterial biofilm compared to titanium [16].…”
Section: Comparison Of Titanium With Other Implant Surface Materialsmentioning
confidence: 95%
“…The difference in results from in vivo , in situ , and in vitro experiments is clear and the interfering factors involved are inclusion criterions established to select the patients, in relation to in vivo and in situ studies, and the number and types of bacteria used to biofilm formation, in case of in vitro study. Freitas et al [30] in 2005 showed that a more rough surface causes an exponential increase in the number of bacterial cells, when just one kind of bacterium, Streptococcus sanguis , was utilized. However, when the study was performed upon the same type of surface, titanium, changing only the roughness value, and using a large number of bacteria species, the roughness does not act as an influential factor.…”
Section: Surface Characteristics Of Abutments Implantsmentioning
confidence: 99%
“…Previous in situ studies conducted for longer periods of time have evaluated only the total microbial counts or a few microbial species and did not considered the biochemical composition of the biofilm . Conversely, a study that conducted a comprehensive microbiologic analysis did not consider the biochemical composition of the biofilm . In addition, none of these studies considered the relevance of dietary carbohydrate in changing the composition of the biofilms formed on titanium surfaces.…”
mentioning
confidence: 99%
“…11,17 Conversely, a study that conducted a comprehensive microbiologic analysis did not consider the biochemical composition of the biofilm. 18 In addition, none of these studies considered the relevance of dietary carbohydrate in changing the composition of the biofilms formed on titanium surfaces.…”
mentioning
confidence: 99%